Fabrication of 3D scaffolds reproducing intestinal epithelium topography by high-resolution 3D stereolithography. (November 2019) - Creff, Justine; Courson, Rémi; Mangeat, Thomas; Foncy, Julie; Souleille, Sandrine; Thibault, C.; Besson, Arnaud; Malaquin, Laurent
Abstract: The small intestine is a complex tissue with a crypt/villus architecture and high tissue polarity. Maintenance of tissue integrity and function is supported by a constant renewal of the epithelium, with proliferative cells located in the crypts and differentiated cells migrating upward to the top of villi. So far, most in vitro studies have been limited to 2D surfaces or 3D organoid cultures that do not fully recapitulate the tissue 3D architecture, microenvironment and cell compartmentalization found in vivo . Here, we report the development of a 3D model that reproduces more faithfully the architecture of the intestinal epithelium in vitro . We developed a new fabrication process combining a photopolymerizable hydrogel that supports the growth of intestinal cell lines with high-resolution stereolithography 3D printing. This approach offers the possibility to create artificial 3D scaffolds matching the dimensions and architecture of mouse intestinal crypts and villi. We demonstrate that these 3D culture models support the growth and differentiation of Caco-2 cells for 3 weeks. These models may constitute a complementary approach to organoid cultures to study intestinal homeostasis by allowing guided self-organization and controlled differentiation, as well as for in vitro drug screening and testing.